KINERJA DINAS KESEHATAN KOTA SEMARANG (Dalam Mengawasi Kualitas Depot Air Minum Isi Ulang) - Dewi, Widia Sari; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2016)
Health is an important investment to support economic development as well as having an important role in poverty reduction efforts. Seeing the importance of the role of health, the Government is obliged to protect and guarantee the citizens of the various problems related to health. This study will analyze the performance conducted by the Health Department of Semarang and aspects that support and hinder the performance of Semarang City Health Office in monitoring the quality of water refill depot. This study uses the theory of organization and five dimensions of performance that productivity, the orientation of the quality of service, responsiveness, responsibility and accountability with qualitative descriptive approach. Data collection techniques used through observation, interviews, documentation and literature study with informants employee Semarang City Health Office. The results show that the performance is done Semarang City Health Office in monitoring the quality of drinking water refill depot can not be said to be good, still found obstacles such as issues of human resources, budget is limited to community participation is minimal. While supporting the performance aspect of Semarang City Health Department in monitoring the quality of drinking water refill depot is already a clear division of labor, discipline and high responsibility held by employees, the fit between health program created by what is needed by the community. Inside overcome these obstacles there are some suggestions that can be done such as identifying water refill depot, to provide guidance and counseling, pemberikan strict sanctions availability of places to submit claims or complaints, providing budget funds to support the monitoring activities refill depot.